VISUALISASI KELEBIHAN PENYANDANG DISABILITAS DALAM GAYA POST IMPRESIONIS - BIMA REKSO WIBOWO, Drs. Idran Wakidi, M.Pd., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of the creation of this final work is to provide learning in life and generate a sense of gratitude for what has been owned. By looking at the physical state of different people. This final paper creation method uses five stages: preparation stage, elaboration stage, synthesis stage, concept realization stage, and completion stage, and lastly hold painting exhibition by using watercolor over canvas with brushstrokes and spontaneity techniques. In the Post-Impressionist flow The visualized work is about physical deformities with different titles but still having a unified entity. Through this painting the author pours the anxiety felt by the painting entitled. (4) Blind, (5) Beautiful Dance, (6) Iron Feet, (7) Glide, (8) Speaking, (9) Not Hearing, (10) Not Speaking.Keywords: Visualization, Disability, Post-Impression,